Manos que bailan : cómo Teresa Carreño tocó el piano para el Presidente Lincoln - Engle, Margarita (Atheneum Books for Young Readers, 2021)
Looks at the life and accomplishments of Teresa Carreño, one of the world's most famous pianists who, by age nine, performed for President Abraham Lincoln at the White House.